2019
DOI: 10.3390/app9163280
|View full text |Cite
|
Sign up to set email alerts
|

Detecting the Void behind the Tunnel Lining by Impact-Echo Methods with Different Signal Analysis Approaches

Abstract: A void behind the lining in a tunnel is considered to be a critical condition as it can significantly impair the tunnel service life. In this study, we adopted the impact-echo (IE) method to detect the voids. We designed two test conditions (tunnel lining with and without a void) for our experiments performed in a laboratory environment. The influences of void size and impact-void position were analysed using numerical simulations. The vibration response signals were analysed in the time, frequency, and time-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The combination of TER and GPR can provide new approaches for voids inspection. Acoustic techniques are important for detecting voids behind linings [23,[93][94][95][96][97][98]. Impact-echo, an acoustic NDT method, is a reliable and widely used method for detecting internal defects in concrete.…”
Section: Voidsmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of TER and GPR can provide new approaches for voids inspection. Acoustic techniques are important for detecting voids behind linings [23,[93][94][95][96][97][98]. Impact-echo, an acoustic NDT method, is a reliable and widely used method for detecting internal defects in concrete.…”
Section: Voidsmentioning
confidence: 99%
“…Carino [93] summarized the theory, numerical simulation, experimental verification, and field demonstrations of the impact-echo method. Cao et al [94] compared several signal analysis approaches used in the impact-echo method for detecting voids behind linings. The experiment showed that the wavelet analysis can provide better energy distribution, and the dynamic stiffness method can determine the location of voids.…”
Section: Voidsmentioning
confidence: 99%
“…Various techniques, including impact-echo, the microtremor method, infrared thermography, ground penetrating radar (GPR), and ultrasonic tomography, have been commonly used for detecting internal defects in tunnel linings [2][3][4][5]. Studies have shown that these methods can effectively detect defects in tunnel linings and achieve satisfactory detection results [6][7][8]. The combination of multiple techniques [9,10] can especially enhance the identification and localization of the defects.…”
Section: Introductionmentioning
confidence: 99%
“…To consider the influence of pile cap in the method, Chu et al [20] performed a laboratory test and a numerical model to investigate the dynamic stiffness of the cappile system. In addition, the dynamic stiffness index was also employed to detect the void behind the tunnel linings [21].…”
Section: Introductionmentioning
confidence: 99%